Aquaponics for Improved Food Security in Africa: A Review - Obirikorang, Kwasi Adu; Sekey, Wonder; Gyampoh, Benjamin Apraku; Ashiagbor, George; Asante, Winston (Frontiers in Sustainable Food Systems, 2021)
Increasing demand on water resources, reduced land water availability, and concerns over food security have spurred the evolution of many innovative and complex food production. An aquaponic system is a productive, innovative, and sustainable fish and vegetable production system that is revolutionizing agriculture in the face of drought, soil fertility losses, and climate change. Aquaponics, as an advanced aquaculture-agriculture system, is expected to improve food security in developing countries. However, as an emerging technology, there is very limited information on the system in Africa. Questions about the ecological and socio-economic sustainability of aquaponics are answered in this comprehensive review. This review considers aquaponics projects in Africa, categorizes the technology by evidences of their effectiveness, fish and plant yields, and juxtaposes the technology within best-use practices to make recommendations that will inform evidence-based policymaking. It also maps the present spatial adoption of the technology in sub-Saharan Africa and highlights the system's contribution to improving food security on the continent. Egypt and South Africa are countries where aquaponics is emerging and being adopted at faster rates and contributing to food security. In West Africa, significantly lower net-discounted benefit-cost ratios were realized when aquaponics systems were constructed using imported materials compared to using locally available materials. Despite aquaponics systems generally having higher start-up costs currently, its potential to be economically viable when undertaken with local materials is very high.